CFD simulation of air to air enthalpy heat exchanger: Variable membrane moisture resistance. (5th June 2015) - AL-Waked, Rafat; Nasif, Mohammad Shakir; Morrison, Graham; Behnia, Masud
Abstract: Conjugate heat and mass transfer processes across membrane heat exchangers of variable mass transportation resistance were investigated numerically. One half of flow channel for the hot stream and another for the adjacent cold stream were simulated. Effects of channel height, Reynolds number and flow direction on heat exchanger thermal effectiveness and energy recovered were studied. The validated CFD model showed that values of moisture resistance decrease with the increase in flow rates and/or the decrease in vapour mass fractions on both sides of the membrane. Furthermore, total hydraulic diameter effects on the thermal efficiency within membrane heat exchangers were found strong. Highlights: CFD simulation of air to air membrane heat exchanger. Heat and mass transfer processes across variable moisture resistance membrane. Effects of membrane material and flow configurations on performance were examined. Results were presented in terms of total effectiveness or thermal energy recovered.